2016
DOI: 10.1016/j.econmod.2015.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Vertical price transmission in the US beef sector: Evidence from the nonlinear ARDL model

Abstract: The objective of this work is to investigate vertical price transmission in the US beef sector. To this end, it employs the Nonlinear ARDL model which allows prices to be tied by asymmetric relationships both in the long-as well as in the short-run. The empirical results indicate the presence of asymmetry in magnitude for the pair of markets farmwholesale and the presence of both asymmetry in speed and asymmetry in magnitude for the pair of markets wholesale-retail. The difference between the long-run elastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 52 publications
3
62
0
1
Order By: Relevance
“…The dynamic multipliers depict the evolution of the dynamic of economic growth following a one-unit shock hitting one of the determinants of economic growth, thus providing the path to the new equilibrium (Fousekis et al 2016). …”
Section: Estimation Strategy and The Datamentioning
confidence: 99%
“…The dynamic multipliers depict the evolution of the dynamic of economic growth following a one-unit shock hitting one of the determinants of economic growth, thus providing the path to the new equilibrium (Fousekis et al 2016). …”
Section: Estimation Strategy and The Datamentioning
confidence: 99%
“…Then, the presence of long-run association between the 7 The ARDL framework can simultaneously resolve the problem of residual serial correlation and endogenous regressors if an appropriate lag order of the ARDL (p, q) model is selected (Pesaran and Shin, 1998). The degree to which any endogeneity is corrected in the asymmetric ARDL framework depends on the integration order of the decomposed series Finally, according to Fousekis et al (2016), the paths of asymmetric adjustments and the duration of the disequilibrium following a positive or a negative shock on the system can provide very useful information regarding asymmetry patterns. These short-run and long-run asymmetry paths can be presented through the cumulative dynamic multiplier effect on for a unit change in !…”
Section: The Bds Test For Non-linearitymentioning
confidence: 99%
“…Most studies focus on price transmission in domestic markets (Fousekis et al, 2016;Pozo et al, 2013;Bakucs and Fertő, 2006;Lloyd et al, 2006;Sanjuan and Dawson, 2003;Goodwin and Holt, 1999;Chang and Griffith, 1998;Griffith and Piggott, 1994). Chang and Griffith (1998) analyzed the transmission relationship between producer price, wholesale price and retail prices of Australian beef based on the monthly data from 1971 to 1994, and found long-term co-integration relationship existing among the three price series.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the transmission relationship between the producer price, the wholesale price and the retail price is symmetric in the United States (US) beef market. Fousekis et al (2016) employed the Nonlinear ARDL model and monthly data for the period 1990 to 2014 and found asymmetry in magnitude for the pair of markets farm-wholesale in the U.S. beef market.…”
Section: Literature Reviewmentioning
confidence: 99%